DETERMINATION OF BOUNDS OF DARKSTRAHLUNG MODEL FROM THE LHC AND FERMI-LAT DATA - Hidayat, Michael
The existence of dark matter in the universe has been proven by various observations at the galaxy scale, the galaxy cluster, and the cosmology scale. Based on the data from Wilkinson Microwave Anisotropy Probe (WMAP), dark matter fills 24% of our universe. Until now, dark matter only interacts gravitationally with the other matters and is hypothezied to interact very weak with the other matters based on Weakly Interacting Massive Particles (WIMP) scenario. The other dark matter’s characteristics, such as its mass, spin, and the other interactions are still elusive. Therefore, in other to get the other dark matter’s characteristic, many assumptions and models are proposed, one of them is the darkstrahlung model. Darkstrahlung model is a model that observes the presence of dark gauge boson from U(1)D group which mixes with U(1)Y standard model particles through a kinetic mixing operator. The interaction between particle with q can be written in the form of effective operator, that is 1 2 V (q q)( ) dan 1 2 A (q